2013
DOI: 10.1016/j.jval.2013.04.002
|View full text |Cite
|
Sign up to set email alerts
|

Validation of Electronic Systems to Collect Patient-Reported Outcome (PRO) Data—Recommendations for Clinical Trial Teams: Report of the ISPOR ePRO Systems Validation Good Research Practices Task Force

Abstract: Outcomes research literature has many examples of high-quality, reliable patient-reported outcome (PRO) data entered directly by electronic means, ePRO, compared to data entered from original results on paper. Clinical trial managers are increasingly using ePRO data collection for PRO-based end points. Regulatory review dictates the rules to follow with ePRO data collection for medical label claims. A critical component for regulatory compliance is evidence of the validation of these electronic data collection… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
56
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 66 publications
(56 citation statements)
references
References 2 publications
0
56
0
Order By: Relevance
“…Thus, such studies may have wider and reassuring implications not only for the DLQI but also for other PROs within dermatology and across other medical specialties, encouraging early simultaneous validation of electronic and paper versions. Several challenges remain, including interface design decisions, data collection and adapting electronic PROs to target populations, particularly in patients with physical disabilities or other impairments . Nevertheless, this study has demonstrated that when DLQI migrates to an electronic format, scores are equivalent despite an overall slower completion time, which should become negligible with increased use and improvements to the app interface.…”
Section: Discussionmentioning
confidence: 86%
“…Thus, such studies may have wider and reassuring implications not only for the DLQI but also for other PROs within dermatology and across other medical specialties, encouraging early simultaneous validation of electronic and paper versions. Several challenges remain, including interface design decisions, data collection and adapting electronic PROs to target populations, particularly in patients with physical disabilities or other impairments . Nevertheless, this study has demonstrated that when DLQI migrates to an electronic format, scores are equivalent despite an overall slower completion time, which should become negligible with increased use and improvements to the app interface.…”
Section: Discussionmentioning
confidence: 86%
“…Notably, when data collection is performed on a wireless web-based application platform, it is necessary to ensure the quality of all electronic systems in each hospital, including application software, server computers, and wireless Internet networking. Recently, the International Society for Pharmacoeconomics and Outcomes Research (ISPOR) ePRO Systems Validation Good Research Practices Task Force reported its recommendations for the validation of electronic systems used to collect PRO data [22]. According to their recommendations, several core elements are necessary for trials to validate electronic PRO administration systems.…”
Section: Discussionmentioning
confidence: 99%
“…(UAT is one aspect of an extensive system/software validation process that is far beyond the scope of this article. Another ISPOR PRO Task Force report, Validation of Electronic Systems to Capture Patient Reported Outcomes (PRO) Data-Recommendations for Clinical Trial Teams: A report of the ISPOR ePRO Systems Validation Task Force [33], addresses this topic.) According to Coons et al [29], "the purpose of UAT is to determine whether the software complies with the written system specification or user requirements document."…”
Section: Usability Versus Feasibilitymentioning
confidence: 99%